Persuade the four-step process to influence people and decisions - Lares, Andres; Cochran, Jeff (John Wiley & Sons, Inc., 2021)
"Persuade draws on psychology, sociology, decision-making, body language, emotional intelligence, and other fields in order to explain why we do what we do, and then ultimately provides readers with an easy-to-use 4-step process for how to influence people. It is uniquely based on the combination of original research, scientific studies, real-world examples, and practical exercises -- making it a fun and easy read that is credible and highly impactful. When selling, buying, negotiating, or generally communicating in business and in life, we aim to achieve our objectives but also walk away, and have the other side walk away, feeling good about the process. There are many excellent business books on negotiation, communication, marketing and sales; however, few explore the common, human mechanisms underlying all of these scenarios in an in-depth, up-to-date scientific-yet-commonsense manner. Persuade will empower readers with an easy-to-use 4-step process, based on original research, scientific studies, real-world examples and practical exercises. Readers will walk away understanding how and why people make decisions, with usable tools to improve their ability to influence others and increase both confidence and success"--